Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - Chapter 11 Review Problem Set - Page 520: 55



Work Step by Step

We first use the FOIL method to simplify the expression. Then, knowing that $i=\sqrt{-1}$, we can substitute $-1$ for $i^{2}$ to obtain: $(6+9i)(-1-i)$ =$6(-1-i)+9i(-1-i)$ =$-6-6i-9i-9i^{2}$ =$-6-15i-9i^{2}$ =$-6-15i-9(-1)$ =$-6+9-15i$ =$3-15i$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.